The Role of Compensation Systems in Enhancing Employee Performance in a Traditional Culinary MSME in Yogyakarta - Filsa, Chan; Sofiati, Sofiati (Research Horizon, 2026)
This study investigates the role of compensation in enhancing employee performance at MSME X, a traditional culinary business in Sleman, Yogyakarta. Although Indonesian MSMEs contribute significantly to employment and regional growth, many face human resource management challenges, particularly ineffective compensation systems. The study aims to analyze how compensation is perceived and implemented to improve performance. Using a qualitative descriptive approach, data were collected through in-depth interviews with five purposively selected informants, consisting of the owner or manager, the human resources department, the production supervisor, the operations supervisor, and frontliner staff, analyzed using the Miles and Huberman method, and validated through triangulation. Findings show that compensation is viewed as a direct consequence of performance, aligned with Vroom’s Expectancy Theory, implemented through monthly KPIs. KPI-based incentives and overtime bonuses are considered most effective, complemented by base salary, attendance allowances, and accommodation facilities functioning as Herzberg hygiene factors, although overtime practices remain not fully compliant. The study validates Vroom and Herzberg’s theories in the Indonesian culinary MSMEs context and suggests structured KPIs, hourly overtime schemes, phased BPJS implementation, and sales training to enhance retention and competitiveness.